A Novel Approach to Method for the Detection of Optic Disc Location in Retinal Images using Image Processing Techniques - Kemal Adem; Mahmut Hekım; Onur Comert; Selim Demır (Journal of New Results in Science)
Biomedical image analysis used for which is applied to assist in clinical diagnosis processes, is one of the research areas that draw intense interest of scientists. The retinal fundus oculi images are used in clinics extensively for the diagnosis and treatment of various eye diseases. The detection of optic disc is one of the most basic steps that should be taken during automatic screening of Diabetic Retinopathy (DR) in particular. In this study, three different solutions are proposed for detecting the optic disc location, using the brightness and circularity properties of the related region. As a result of the comparison of the findings of these three experiments, the Circular Hough Transform method applied with HSV color space is was found to be more successful by 99.16% accuracy, and therefore it is proposed as a viable method for the detection of optic disc.